Peran Guru Agama dalam Menanamkan Pendidikan Karakter yang Berbasis Nilai Agama dan Budaya Sasak pada Siswa Kelas VI SDN 5 Ampenan Kota Mataram - Zaenal Abidin (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to examine the role of Islamic religious teachers in instilling character education based on religious values and Sasak culture in sixth-grade students at SDN 5 Ampenan, Mataram City. Character education is a fundamental pillar in shaping students' personalities, and religious teachers occupy a strategic position in this process, especially within the context of the Sasak community, which is rich in Islamic values and local wisdom. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. Research subjects included the principal, the Islamic Education (PAI) teacher, and sixth-grade students. Findings reveal that religious teachers serve as: (1) educators and instructors of Islamic values; (2) moral role models grounded in Sasak culture; (3) motivators in the internalization of values such as tata krama (etiquette), titi (prudence), and tatas tuhu trasna (honesty, loyalty, and compassion); and (4) facilitators of religious and local cultural activities. Supporting factors include principal support, an Islamic school environment, and preserved local wisdom. Inhibiting factors include social media influence and a lack of Sasak culture-based learning resources. This study recommends the systematic integration of Sasak cultural values into the Islamic religious education curriculum at the primary school level.